Porphyromonas gingivalis coinfects with KSHV in oral cavities of HIV+ patients and induces viral lytic reactivation. Issue 12 (2nd June 2020) - Dai, Lu; Barrett, Lindsey; Plaisance‐Bonstaff, Karlie; Post, Steven R.; Qin, Zhiqiang
Abstract: Kaposi's sarcoma‐associated herpesvirus (KSHV) infection causes several human cancers, including Kaposi's sarcoma (KS), one of the most common AIDS‐associated tumors. The involvement of the oral cavity represents one common clinical manifestation of AIDS‐KS individuals with periodontal diseases and an oral carriage of a variety of pathogenic bacteria, including Porphyromonas gingivalis . In the current study, we report the clinical relevance of P. gingivalis and KSHV coinfection in the oral cavity of a cohort of HIV+ patients. Furthermore, we found that P. gingivalis conditioned medium or derived lipopolysaccharide effectively induced KSHV lytic reactivation from infected oral cells. This reactivation requires TLR4 as well as the activities of p38 and Jun N‐terminal kinase‐ mitogen‐activated protein kinase signaling pathways. Our findings reveal the mechanisms through which coinfected periodontal pathogens potentially promote oncogenic virus pathogenesis in the unique niche of immunocompromised patients. Highlights: Porphyromonas gingivalis co‐infects with KSHV in the oral cavities of some HIV+ patients. P. gingivalis induces KSHV lytic reactivation from infected oral cells through manipulation of host signaling pathways.